2005
DOI: 10.1055/s-2005-837525
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulates the Reproductive Male Axis in Rats during Sexual Maturation by Acting on Hypothalamic Excitatory Amino Acids

Abstract: The purpose of the present study was to determine the effect of treatment with leptin on gonadotrophin secretion and hypothalamic GnRH, excitatory and inhibitory amino acids release, in prepubertal (15 days old) and peripubertal (30 days old) male rats. Rats of both ages received a single (ip) injection of 30 microg/kg leptin 60 minutes previous to sacrifice. Serum LH was determined, and the hypothalamus dissected and incubated in Earle's medium. GnRH and amino acids release were determined in the media. LH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…CDGP is a variation of the onset and timing of pubertal development without a defined endocrine abnormality. Recently published results showed that both leptin and ghrelin have a role in GnRH production at different reproductive stages [18,20,21]; they showed opposing effects on pulsatile GnRH secretion [18]. We hypothesized that low leptin and high ghrelin concentrations could be implicated in altering the tempo of puberty in adolescents with CDGP.…”
Section: Discussionmentioning
confidence: 99%
“…CDGP is a variation of the onset and timing of pubertal development without a defined endocrine abnormality. Recently published results showed that both leptin and ghrelin have a role in GnRH production at different reproductive stages [18,20,21]; they showed opposing effects on pulsatile GnRH secretion [18]. We hypothesized that low leptin and high ghrelin concentrations could be implicated in altering the tempo of puberty in adolescents with CDGP.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has facilitatory effects on GnRH secretion and is considered to be an important regulator of GnRH and gonadotrophin secretion. 9,28 Low leptin levels would therefore contribute to a hypogonadal state and low levels of gonadal steroids. It is interesting that in our study, leptin was an independent predictor of E 2 but not of testosterone, and that when fat mass was added to the model, this replaced leptin as an independent predictor of E 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,13,[24][25][26][27] Additionally, leptin and ghrelin showed opposing effects on pulsatile GnRH secretion. 9 Furthermore, obese children have early puberty that could be the effect of high circulating levels of leptin.…”
Section: Discussionmentioning
confidence: 99%